Iron, inflammation and atherosclerosis risk in men vs. perimenopausal women. Issue 1 (July 2015) - Raman, Subha V.; Sharkey-Toppen, Travis P.; Tran, Tam; Liu, Jim X.; McCarthy, Beth; He, Xin; Smart, Suzanne; Gulati, Martha; Wexler, Randell; Simonetti, Orlando P.; Jackson, Rebecca D.
Abstract: Objective: Age at first atherosclerotic event is typically older for women vs. men; monthly iron loss has been postulated to contribute to this advantage. We investigated the relationship between an MRI-based arterial wall biomarker and the serum inflammatory biomarker high-sensitivity C-reactive protein (hsCRP) in perimenopausal women vs. men. Methods and Results: Women without evident atherosclerotic disease were prospectively enrolled and observed over 24 months of menopause transition, indicated by hormone levels and reduction in median number of menstrual cycles from 4 [3–6] per year to 0 [0–1] per year ( P  < 0.01). Higher hsCRP predicted shorter carotid artery wall T2* in women entering the menopause transition (r = −0.3139, P  = 0.0014); this relationship weakened after 24 months of perimenopause in women (r = −0.1718, P  = 0.0859) and was not significant in a cohort of men matched for age and cardiovascular risk category (r = −0.0310, P  = 0.8362). Serum ferritin increased from baseline to 24-month follow-up during women's menopause transition (37 [20–79] to 67 [36–97] ng/mL, P  < 0.01), but still remained lower compared to men (111 [45–220] ng/mL, P  < 0.01). Circulating ferritin levels correlated with arterial wall T2* values in women at baseline (r = −0.3163, P  = 0.0013) but not in women after 24 months (r = −0.0730, P  = 0.4684) of menopause transition nor in men (r = 0.0862, P  = 0.5644). Conclusions: An arterial wall iron-based imaging biomarker reflects degree of systemic inflammation in younger women, whereas this relationship is lost as women transition through menopause to become more similar to men. Iron homeostasis and inflammation in the arterial wall microenvironment warrants further investigation as a potential early target for interventions that mitigate atherosclerosis risk. Graphical abstract: Highlights: Iron balance may influence women's older age at first atherosclerotic event vs. men. A magnetic resonance arterial wall biomarker sensitive to endogenous iron was used. Arterial wall MRI-T2* parallelled hsCRP in early but not later menopause nor in men. Ferritin's link to MRI-T2* in women was lost after 2 years and was absent in men. Targeting iron homeostasis to lower incident atherosclerosis warrants further study.